Detecting patterns of local raw material utilization among informal lithic assemblages at the late Paleolithic site of Shuidonggou Locality 2 (China). (March 2019) - Lin, Sam C.; Peng, Fei; Zwyns, Nicolas; Guo, Jialong; Wang, Huimin; Gao, Xing
Abstract: The apparent simplicity and the lack of changes in stone tool production during the Paleolithic in China is often explained by environmental, subsistence and demographic processes that either promoted a casual approach to lithic technological organization or impeded cultural innovation among East Asian hominin groups. This perspective stems from an assumption that complexity in lithic management is solely reflected in formalized core reduction methods, tool typology and/or the transport of non-local raw material types. In this study, by using survey to establish the baseline expectation of local raw material proportions, we demonstrate the differential treatments of locally abundant stone types at the Late Paleolithic site of Shuidonggou Locality 2. In spite of the apparent technological stasis, we observe shifting patterns of local raw material selection and transport during late Marine Isotope Stage 3. Hence our results suggest that, in basic core-and-flake assemblages, technological complexity is expressed in the selection, use and transport of lithic resources, including informal artifacts made on locally available raw material. Highlights: Shuidonggou Locality 2 shows the persistence of a basic core-and-flake technology. Raw material survey establish baseline variation for volume proportion and geometry. Results show instances of archaeological assemblages deviate from the baselines. Differential utilization of local stone types despite limited technological change.